Interdisziplinäre Interaktionen und Kooperationen von Lehrkräften in Communities of Practice: Wie lassen sie sich erfassen und beschreiben? - Ritter, Rosi; Habrainski, Ewa; Schwarze, Cordula; Fussangel, Kathrin (Glottodidactica, 2025)
This article presents the development and testing of a category system developed on the basis of educational science-oriented co-construction research and conversation analysis research. The aim is to record cooperation processes in communities of practice as cooperative settings in which teachers are working together intensively. Based on the approach of co-construction as an intensive form of cooperation, the paper describes how teachers in such communities jointly develop knowledge and materials. The category system presented here was developed and tested on the basis of recorded interactions between different communities of practice that jointly constructed language teaching materials as part of a project. The data was analysed in two steps – first by identifying the phenomena inherent in the conversation and then coding them with a category system based on conversation and co-construction theory. The category system is described, with its central and superordinate categories, and exemplary coded sequences are used to illustrate that the developed categories are suitable for describing the interactions with regard to content-related and conversation-analytical characteristics.